Pola Komunikasi Orang Tua Terhadap Anak Remaja dalam Mengatasi Judi Online di Desa Lalang Kecamatan Rana Mese Kabupaten Manggarai Timur - Hilda Yoma Daiman (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
Family communication plays a crucial role in shaping the character and behavior of adolescents, especially in facing social challenges such as online gambling. This study aims to determine how parental communication patterns influence adolescents' involvement in online gambling activities in Lalang Village, Rana Mese District, East Manggarai Regency. Furthermore, this study also identifies various efforts made by parents to address this problem. The method used was a descriptive qualitative approach, with data collection through interviews, observation, and documentation. The results indicate four family communication patterns implemented by parents: pluralistic, consensual, protective, and laissez-faire. The pluralistic pattern is characterized by open communication and equal discussion, which encourages children to avoid online gambling. The consensual pattern combines warm communication with an emphasis on shared values. Conversely, the protective pattern tends to be dominant, where parents supervise without providing space for dialogue, resulting in children becoming withdrawn. The laissez-faire pattern, with minimal communication, makes children feel free to engage in gambling. This study uses the symbolic interaction theory, namely mind, self, and society. In addition to communication patterns, this study also found that parents undertake various efforts, such as limiting digital device use, providing advice, and increasing supervision of their children's social environment. These efforts demonstrate that their effectiveness is highly dependent on the quality of communication within the family.